IMPLIKASI KONSEP UTILITARIANISME DALAM PENGELOLAAN SUMBERDAYA HUTAN TERHADAP MASYARAKAT ADAT - Aminah Aminah (Faculty of Law, Universitas Diponegoro, 2014)
Policy in the sector of forestry aimed at the overall prosperity of the people in its implementation has caused the exploitation of economic oriented, causing deforestation, environment destruction, and ignore the existence of indigenous people. It indicates that the government is more focus on the base of Utilitarian political value that can justify the sacrificed of the weak and unpopular for the benefit of the majority. The Utilitarian does not ensure justice, so that to save the indigenous people from the threat of extinction, the formation of policies requires the development principle of justice, especially for equal access of all groups and community to participate in determining natural resource management policies, and to utilize the natural resources